Using Plants of Novel Ecosystems as Resources to Create Green Roofs in Cities’ Adaptation to the Climate Change Process - Magdalena Biela; Edyta Sierka (Studia Ecologiae et Bioethicae)
Using local wild plant resources to create green roofs in urban areas is a sustainable solution that supports cities' adaptation strategies to climate change. Creating extensive green roofs, in accordance with the Nature-Based Solutions concept, supports minimizing the effects of climate change, loss of biodiversity and human health. The aim of this paper is to identify, based on an analysis of published research results, the main criteria for selecting vegetation introduced to green roofs and the role of green roofs in minimizing the effects of climate change in the context of NBS. The data were collected by analyzing the results of studies published in the last 10 years, focusing on plant selection. It was found that species selection often fails to consider plant functional traits. The potential of wild plants in urban-industrial areas for creating green infrastructure and optimizing ecosystem services remains largely unrecognized. However, certain plants with desirable functional traits, originating e.g. from habitats such as post-industrial coal mining waste heaps, show promise in providing functional support to urban ecosystems in minimizing the effects of climate change.